2012
DOI: 10.1128/jb.00713-12
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoketolase Pathway for Xylose Catabolism in Clostridium acetobutylicum Revealed by 13 C Metabolic Flux Analysis

Abstract: b Solvent-producing clostridia are capable of utilizing pentose sugars, including xylose and arabinose; however, little is known about how pentose sugars are catabolized through the metabolic pathways in clostridia. In this study, we identified the xylose catabolic pathways and quantified their fluxes in Clostridium acetobutylicum based on [1-13 C]xylose labeling experiments. The phosphoketolase pathway was found to be active, which contributed up to 40% of the xylose catabolic flux in C. acetobutylicum. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
54
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 51 publications
(70 reference statements)
6
54
1
Order By: Relevance
“…Flux distributions under different sugar media were calculated from the following steady-state 13 C-labeling experiments: [ We constructed a carbon mapping model to calculate the fluxes through PKP, PPP, and upper glycolysis from the labeling patterns of ribose-5-phosphate (R5P), Xu5P, glucose-6-phosphate (G6P), fructose-1,6-bisphosphate (FBP), dihydroxyacetone-phosphate (DHAP), and 3-phosphoglycerate (3-PG) (see Fig. S2 in the supplemental material).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Flux distributions under different sugar media were calculated from the following steady-state 13 C-labeling experiments: [ We constructed a carbon mapping model to calculate the fluxes through PKP, PPP, and upper glycolysis from the labeling patterns of ribose-5-phosphate (R5P), Xu5P, glucose-6-phosphate (G6P), fructose-1,6-bisphosphate (FBP), dihydroxyacetone-phosphate (DHAP), and 3-phosphoglycerate (3-PG) (see Fig. S2 in the supplemental material).…”
Section: Methodsmentioning
confidence: 99%
“…Historically, it was assumed that carbons from Xyl and Arab pass from the PPP through glycolysis to supply acidogenesis and solventogenesis. However, two recent studies (5,13) reported that acids and solvents can be produced from these sugars from a glycolysis-independent pathway, the phosphoketolase pathway (PKP) (Fig. 1B).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Xylose-specific transporters and high-affinity transporters of xylose were developed by evolution of xylose-utilizing yeast, directed evolution or rational design of glucose transporters [23][24][25][26][27]. Except for transporter engineering, reconstitution of carbohydrate metabolic networks, such as the phosphoketolase pathway, is another approach to improve xylose utilization [15,28]. Recently, it has been reported that disruption of some genes in glycolysis and pentose phosphate (PP) pathway resulted in simultaneous xylose and glucose utilization [5,29].…”
Section: Introductionmentioning
confidence: 99%